2019
DOI: 10.1021/acscatal.9b04063
|View full text |Cite
|
Sign up to set email alerts
|

Controlling and Stabilization of Ru Nanoparticles by Tuning the Nitrogen Content of the Support for Enhanced H2 Production through Aqueous-Phase Reforming of Glycerol

Abstract: The stable activity of catalysts is an important issue in catalysis, particularly aqueous-phase reforming (APR) of renewable oxygenates, of biomass origin, to get H2. Sintering of metal nanoparticles on supports affects catalyst stability. To alleviate this problem, a series of highly stable Ru-supported catalysts with controlled metal nanoparticle sizes have been prepared via the easy incipient wetness impregnation method. These catalysts were used for APR of glycerol to produce H2. Nitrogen-doped mesoporous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 86 publications
1
35
0
Order By: Relevance
“…The D‐band to the G‐band intensity ratios (I D /I G , understood via the collective areas of the band) are 1.62, 1.72, 2.31, 2.42, 2.40 and 2.38 for MC, Au‐MC‐SI, NMC, Au‐NMC‐SI, Au‐NMC‐DP and Au‐NMC‐IW, respectively. This result revealed that imperfection in the graphite‐like sheets was raised on increasing the N‐content of the catalyst as well as after Au metal loading [67,76–79] …”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The D‐band to the G‐band intensity ratios (I D /I G , understood via the collective areas of the band) are 1.62, 1.72, 2.31, 2.42, 2.40 and 2.38 for MC, Au‐MC‐SI, NMC, Au‐NMC‐SI, Au‐NMC‐DP and Au‐NMC‐IW, respectively. This result revealed that imperfection in the graphite‐like sheets was raised on increasing the N‐content of the catalyst as well as after Au metal loading [67,76–79] …”
Section: Resultsmentioning
confidence: 91%
“…This can be elucidated by means of enhance in the “d electrons density” with shrinking Au nanoparticles size [89] . Additionally, Au nanoparticles are possibly electronically rich due to the transfer of electron density from nitrogen atoms [67,76,84b] . The higher electron density on Au nanoparticles can appreciably affects the binding energies [84b] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[103] The N-doped mesoporous carbon-supported Ru nanoparticles showed higher stability compared to the undoped carbon support during glycerol reforming. [104] The Ndoped CNT-supported Pd nanoparticles showed stability against sintering during nitrobenzene hydrogenation reaction. [105] The functionalization of the support materials has also been shown to improve the metal-support interactions and the metal nanoparticles stability in several important chemical transformations.…”
Section: Improving the Stability Of Supported Metal Catalystsmentioning
confidence: 99%